The use of credit claims as collateral for Eurosystem credit operations - Kentaro Tamura; Evangelos Tabakis (European Central Bank (ECB), 2013)
Credit claims (or bank loans) represent a large share of the collateral accepted by the Eurosystem in its credit operations in recent years. Hence the techniques and procedures used in the use of credit claims as collateral have become significant elements of the monetary policy implementation mechanism in the euro area. The procedures involved in credit claim collateralisation, however, are generally more complex than those for marketable assets traded in regulated markets or in other markets accepted by the Eurosystem. While several types of credit claims are eligible as Eurosystem collateral, each type of credit claim has different characteristics which require specific considerations in the eligibility assessment. This paper provides an overview of the issues involved in the use of credit claims as collateral and relates these to some measures taken by both the public and the private sector aimed at facilitating their use in the euro area. The paper also elaborates on the syndicated loan market in the euro area as this market is sizeable, while it appears that the use of such loans as collateral remains limited.
Keywords: G10; G12; G13; 330; central bank collateral eligibility; Credit claim; syndicated loan; Kreditsicherung; Kreditpolitik; Eurozone